Are Options on Index Futures Profitable for Risk‐Averse Investors? Empirical Evidence - CONSTANTINIDES, GEORGE M.; CZERWONKO, MICHAL; CARSTEN JACKWERTH, JENS; PERRAKIS, STYLIANOS (Journal of Finance, 2011)
ABSTRACT American options on the S&P 500 index futures that violate the stochastic dominance bounds of Constantinides and Perrakis (2009) from 1983 to 2006 are identified as potentially profitable trades. Call bid prices more frequently violate their upper bound than put bid prices do, while violations of the lower bounds by ask prices are infrequent. In out‐of‐sample tests of stochastic dominance, the writing of options that violate the upper bound increases the expected utility of any risk‐averse investor holding the market and cash, net of transaction costs and bid‐ask spreads. The results are economically significant and robust.